Family PArtners in Lifestyle Support (PALS): Family‐based weight loss for African American adults with type 2 diabetes. Issue 1 (2nd December 2016) - Samuel‐Hodge, Carmen D.; Holder‐Cooper, Judith C.; Gizlice, Ziya; Davis, Gwendolyn; Steele, Sonia P.; Keyserling, Thomas C.; Kumanyika, Shiriki K.; Brantley, Phillip J.; Svetkey, Laura P.
Abstract : Objective: To develop and test a family‐centered behavioral weight loss intervention for African American adults with type 2 diabetes. Methods: In this randomized trial, dyads consisting of an African American adult with overweight or obesity and type 2 diabetes (index participant) paired with a family partner with overweight or obesity but not diagnosed with diabetes were assigned in a 2:1 ratio to a 20‐week special intervention (SI) or delayed intervention (DI) control group. The primary outcome was weight loss among index participants at the 20‐week follow‐up. Results: One hundred eight participants (54 dyads—36 (SI) and 18 (DI) dyads) were enrolled: 81% females; mean age, 51 years; mean weight, 103 kg; and mean BMI, 37 kg/m 2 . At post‐intervention, 96 participants (89%) returned for follow‐up measures. Among index participants, mean difference in weight loss between groups was −5.0 kg, P < 0.0001 (−3.6 kg loss among SI; 1.4 kg gain in DI). SI index participants showed significantly greater improvements in hemoglobin A1c, depressive symptoms, family interactions, and dietary, physical activity, and diabetes self‐care behaviors. SI family partners also had significant weight loss (−3.9 kg (SI) vs. −1.0 kg (DI), P = 0.02). Conclusions: A family‐centered, behavioral weight loss intervention led to clinically significant short‐term weight loss among family dyads.